2018
DOI: 10.17159/2078-5151/2018/v56n4a2766
|View full text |Cite
|
Sign up to set email alerts
|

A teenager with ductal carcinoma in situ arising in a fibroadenoma: a case report

Abstract: Breast cancer arising within fibroadenomas (BcaFad) is a very rare finding. BcaFad occurs mostly in women between the ages of 40 and 50. This report details the unique case of an 18-year-old woman with bcafad. We present an 18-year-old woman with a ductal carcinoma in situ (DCIS) arising within a fibroadenoma. This is the youngest reported case of BcaFad in the literature. Clinically, the mass presented characteristics of a benign breast lump. Microscopically, an atypical proliferation of luminal epithelial ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 16 publications
0
4
0
3
Order By: Relevance
“…The average age of patients with Bcafad is in the fifties. A case of Bcafad in an 18-year-old girl was recently reported [3]. To our knowledge, we report the first case occurring in a 15-year-old girl in the literature.…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…The average age of patients with Bcafad is in the fifties. A case of Bcafad in an 18-year-old girl was recently reported [3]. To our knowledge, we report the first case occurring in a 15-year-old girl in the literature.…”
Section: Introductionmentioning
confidence: 72%
“…Management depends on the stage of the disease, but also changes in body image, sexual functioning and the risk of infertility must be taken into account [12] [13]. Oliver Frisch reported a case of Bcafad in an 18-year-old girl with carcinoma in situ whose treatment was surgery alone [3]. Our patient received neoadjuvant chemotherapy with 5-Fluorouracil, Adribalstine and Cyclophosphamide followed by mastectomy and lymph node dissection.…”
Section: Discussionmentioning
confidence: 96%
“…It is uncertain whether FA increases the likelihood of breast cancer development [ 9 ]. Dupont et al reported that the risk of developing invasive breast cancer (IBC) is about 2.17 times greater among patients with FA in comparison to non-fibroadenoma patients [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Approximately two-thirds of carcinomas within FAs are lobular, and the remaining one-third are ductal or mixed [ 12 ]. Malignant changes within FAs typically occur at an older age, with the age of detection in the fifth decade [ 9 , 13 ]. Complex FAs have a higher tendency for malignant transformation than non-complex FAs [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…A faixa etária mais acometida é dos 40 aos 45 anos, isto é, 15 a 20 anos após a média de idade de ocorrência do fibroadenoma. 1 Foi encontrado apenas um relato, de uma jovem adolescente com fibroadenoma associado a um carcinoma ductal in situ 6 .…”
Section: Introductionunclassified